Assessment of the Techno-economic Viability to Produce Biohydrogen from Biowaste - Max J.A. Romero; Elisabetta Arato (Chemical Engineering Transactions)
The adoption of effective strategies to reduce the production costs of renewable H2 and increase its competitive position compared to fossil-based H2 in hard-to-abate sectors is a priority of the European Union. One of these strategies can be to diversify the use of renewable electricity by using other renewable resources such as biomass to produce biohydrogen. The aim of this paper was to assess the technical and economic performance of H2 production by steam reforming (SR) of natural gas as well as three biohydrogen production systems using the levelized cost of H2 (LCOH) as a methodology. Based on a 2,700 Kg H2/h facility, LCOH results showed that bio-oil reforming (€ 3.56/kg) is the least expensive way to produce biohydrogen compared to biomass gasification (€ 4.08/kg) and biogas reforming (€ 4.52/kg). Furthermore, the bio-oil reforming pathway provided an LCOH quite similar to the LCOH obtained by SR of natural gas (€ 3.52/kg), indicating that its use could be viable hard-to-abate sectors.